(3ecGaMI ZSjd GdCehGd (B:s (3WHbG ddbGfhf GdchjJj Qbe (B35 (3dSfI (B2002 (3ebGQfG Hcd ef GdbGfhf GdeUQj hGddHfGfj hGdEeGQGJj (B/s - (3eMeOjf, LdGd haGAs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2004)
(3GdJYQja HZSjd GdCehGd,LQGFe ZSjd GdCehGd hGdYbGH YdjgG,LQGFe ZSjd GdCehGd,GdYbhHGJ,GdJRGeGJGdHfhc hGdeDSSGJ GdeGdjI hGdLRGAGJ , GdJRGeGJ GdHfhc hGdeDSSGJ GdeGdjI GdchjJjI,GdLRGAGJ aj GdbGfhf GdchjJj, GdEdJRGeGJ hGdLRGAGJ aj GdbhGfjf GdCNQi,CfeGW GdeYGedGJ GdeTHhgI dZSjd GdCehGd hGdJMQj hGdEHdGZ YfgG,CfeGW ef GdeYGedGJ GdeTHhgI dZSjd GdCehGd,GdJMQj hGdEHdGZ Yf GdeYGedGJ GdeTHhgIs
(3HjHdjhZQGajG U(B.150s
Keywords: (3GdEeGQGJs; (3JHjjV GdGehGds; (3LQGFe GdGehGds; (3bGfhfs; (3dHfGfs; (3eUQs